Yorkie-Warts Complexes are an Ensemble of Interconverting Conformers Formed by Multivalent Interactions. Issue 4 (19th February 2021) - Baker, Kasie; Kwok, Ethiene; Reardon, Patrick; Rodriguez, Diego J.; Rolland, Amber D.; Wilson, Jesse W.; Prell, James S.; Nyarko, Afua
Graphical abstract: Highlights: Multivalent WW- PPXY complexes regulate critical steps in the cell life cycle. Complex assembly in the context of multivalent binding domains is poorly understood. Multivalent binding of 2 Yorkie WW domains and 5 Warts PPXY motifs was characterized. The two proteins assemble to produce an ensemble of interconverting complexes. The results provide foundational insight into the regulation of WW- PPXY complexes. Abstract: Multiple copies of WW domains and PPXY motif sequences are often reciprocally presented by regulatory proteins that interact at crucial regulatory steps in the cell life cycle. While biophysical studies of single WW domain-single PPXY motif complexes abound in the literature, the molecular mechanisms of multivalent WW domain- PPXY assemblies are still poorly understood. By way of investigating such assemblies, we characterized the multivalent association of the entire cognate binding domains, two WW sequences and five PPXY motifs respectively, of the Yorkie transcription coactivator and the Warts tumor suppressor. Isothermal titration calorimetry, sedimentation velocity, size-exclusion chromatography coupled to multi-angle light scattering and native-state mass spectrometry of Yorkie WW domains interactions with the full-length Warts PPXY domain, and numerous PPXY motif variants of Warts show that the two proteins assemble via binding of tandem WW domains to adjacent PPXY pairs to produce an ensemble of interconverting complexes of variable stoichiometries, binding energetics and WW domain occupancy. Apparently, the Yorkie tandem WW domains first target the two adjacent PPXY motifs at the C-terminus of the Warts polypeptide and additional WW domains bind unoccupied motifs. Similar ensembles of interconverting conformers may be common in multivalent WW domain- PPXY interactions to promote the adaptability and versatility of WW domain- PPXY mediated cellular processes.